The Formations of Masculinities - Bozsó, Georgina (Hungarian Journal of English and American Studies, 2020)
Book review: Horlacher, Stefan, ed. Configuring Masculinity in Theory and Literary Practice. DQR Studies in Literature 58. Boston: Brill Rodopi, 2015. viii + 318 pages. ISBN 978-90-04-29899-6. Hb. 106.